Postantifungal effect of anidulafungin against Candida albicans, Candida dubliniensis, Candida africana, Candida parapsilosis, Candida metapsilosis and Candida orthopsilosis - Gil-Alonso, Sandra (Rev Esp Quimioter, 2019)
OBJECTIVES: Candida albicans remains the most common aetiology of invasive candidiasis, leading to high morbidity and mortality. Nevertheless, the incidence of candidiasis due to non-C. albicans species, such as Candida parapsilosis, is increasing. Postantifungal effect (PAFE) is relevant for establishing dosage schedules in antifungal therapy, as the frequency of antifungal administration could change depending on PAFE. The aim of this study was to evaluate the PAFE of anidulafungin against C. albicans, Candida dubliniensis, Candida africana, C. parapsilosis, Candida metapsilosis and Candida orthopsilosis. MATERIAL AND METHODS: Twenty-one Candida strains were evaluated. Cells were exposed to anidulafungin for 1 h at concentrations ranging from 0.12 to 8 mg/L for PAFE studies. Time-kill experiments (TK) were conducted at the same concentrations. The experiments were performed using an inoculum of 1-5 x 10(5) cells/mL and 48 h incubation. Readings of PAFE and TK were done at 0, 2, 4, 6, 24 and 48 h. RESULTS: Anidulafungin was fungicidal against 2 out of 14 (14%) strains of C. albicans related species in PAFE experiments. Moreover, 2 mg/L of anidulafungin exerted a prolonged PAFE (≥ 33.6 h) against 13 out of 14 (93%) strains. Similarly, fungicidal endpoint was achieved against 1 out of 7 (14%) strains of C. parapsilosis complex, being PAFE prolonged (≥ 42 h) against 6 out of 7 (86%) strains. CONCLUSIONS: Anidulafungin induced a significant and prolonged PAFE against C. albicans and C. parapsilosis and their related species.